The Legality of Collateral Auction by Rural Banks Without Credit Restructuring: A Case Study of Decision No. 260/Pdt.G/2019/PN Dps - Sinaga, Bachtiar Hasan; Purba , Hasim; Lisa Andriati, Syarifah; Gunaika, Raka (Universitas Islam Negeri Raden Intan Lampung, 2025)
Auctions of collateral by Rural Credit Banks (BPR) without going through a credit restructuring process raise legal issues related to debtor protection and the fulfillment of the principle of fairness in banking practices. This study aims to analyze the legality of auctions of collateral by BPR without prior credit restructuring, focusing on Decision Number 260/Pdt.G/2019/PN Dps. The research method used is a normative legal research method, applying the Theory of Statement, Legal Certainty, and Justice to discuss legal issues concerning the validity of collateral auctions without restructuring. This study relies on previously available information (secondary sources). Data collection was conducted through document review and relevant literature, while data analysis techniques were performed using qualitative data analysis. The results of this study include: Credit restructuring is not required in cases of non-performing loans, in accordance with Bank Indonesia Regulation No. 14/15/PBI/2012. This means that banks can auction collateral immediately without restructuring if there is no agreement between the bank and the debtor. Regarding collateral auctioned without prior restructuring, debtors may pursue legal remedies, both non-litigious and litigious. In accordance with Article 21(1) of the Indonesian Financial Services Authority Regulation No. 33/Pojk.03/2018 regarding the Quality of Productive Assets and the Formation of Provisions for the Write-off of Productive Assets of Rural Banks (BPR), the auction conducted by PT. BPR without credit restructuring is valid.